Biological activities and mode of action of lignans from the Piperaceae. - Bourret-Bernard, Claude. (University of Ottawa (Canada), 1995)
Tropical American Piper spp. have insecticidal activities comparable to those of previously studied African and Asian species. Effects of dietary administration of the crude ethanolic extracts of Piper spp. to the European corn borer, Ostrinia nubilalis Hubner, include a reduction of larval growth, a high death rate of larvae, pupae and adults, and a limited effect on the consumption and digestion of food. Among 16 Piper extracts the most active American species were, in decreasing order of growth reducing activity: P. tuberculatum, P. aduncum, P. pseudo-lindenii, P. lanceiaifolium, P. guanacastensis, P. decurrens, P. carilloanum, and P. auritum. Bioassay-guided isolation, using mosquito larvae, led to the isolation of a monolignan, dillapiol, as an active principle of P. aduncum, two neolignans as active principles of P. decurrens, and an amide, piperlonguminine as an active principle of P. tuberculatum. The new isolation of the neolignans and the amide gives further evidence of the biological significance of these two classes of compounds as chemical defenses of the piperaceae. The activities of a series of 15 pure monolignans, lignans, and neolignans were investigated with the polyphagous lepidopteran herbivore, the European corn borer, which has a high adaptive capacity to tolerate plant allelochemicals. The lignans (at a dose of 100 $\mu$g/g in the diet) were generally not highly toxic to the larvae, except for the monolignan dillapiol. However, delayed toxicity was revealed as mortality increased later in the life cycle, reaching at the adult stage a cumulative mortality of 95%, 68%, 60%, 43% and 40% with dillapiol, epiashantin, podophyllotoxin, epiyangambin and cubebin, respectively. The growth profile of larvae further showed that lignans are slow acting toxins, except for dillapiol and cyclolignans of the podophyllotoxin series. Antifeedant activity of the lignans was generally poor. Cubebin was the most active antifeedant with respect to the ECB with a protective concentration, PC$\sb{50}$, of 74 $\mu$g/g. There was a trend of increasing toxicity of lignans which generally parallelled the evolutionary advancement in biosynthesis. Because of their role in reversing insecticide resistance, lignans were tested for their activity on multidrug resistant (MDR) cells with overexpression of the membrane P-glycoprotein. MDR cells responded to the group of cyclolignans in a way similar to the response of other drugs which belong to the multiresistant group, while they showed important collateral sensitivity to the furans and even more to the monolignan dillapiol. An increased uptake of the anticancer drug vinblastine was observed upon co-administration of dillapiol. This activity constitutes a novel mode of action of this lignan, and possibly other insecticide synergists such as piperonyl butoxide, with regards to resistance to drugs and insecticides.
Keywords: Biology, Ecology.